1998
DOI: 10.1183/09031936.98.12010159
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of salbutamol to nonventilated preterm infants by metered-dose inhaler, jet nebulizer, and ultrasonic nebulizer

Abstract: To identify the most efficient device for the delivery of bronchodilator aerosol to nonventilated preterm infants with chronic lung disease, we compared the metered dose inhaler (MDI) used in conjunction with a non-valved spacer, an ultrasonic nebulizer with a small medication cup, and two jet nebulizers. The subjects were enrolled in two double-blind randomized crossover studies. In study A (n=10), each infant was given a nominal dose of 200 microg of salbutamol by a MDI (Ventolin) at 4 h intervals, and in ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 27 publications
1
21
0
1
Order By: Relevance
“…6 Fok et al, in 2 in vivo studies (animal and neonatal), demonstrated a several-fold higher pulmonary deposition of ultrasonic nebulizers, compared to a jet nebulizer. 17,18 Our data are in agreement with their findings. Our data are also in partial agreement with results from Ari et al, who found in an adult mechanical ventilation model that the vibrating mesh outperformed the jet nebulizer but not the ultrasonic nebulizer when the devices were placed either at the Y-piece or 15 cm before the Y-piece.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…6 Fok et al, in 2 in vivo studies (animal and neonatal), demonstrated a several-fold higher pulmonary deposition of ultrasonic nebulizers, compared to a jet nebulizer. 17,18 Our data are in agreement with their findings. Our data are also in partial agreement with results from Ari et al, who found in an adult mechanical ventilation model that the vibrating mesh outperformed the jet nebulizer but not the ultrasonic nebulizer when the devices were placed either at the Y-piece or 15 cm before the Y-piece.…”
Section: Discussionsupporting
confidence: 92%
“…[6][7][8]11,12,[16][17][18] However, there is paucity of data on the newly available technologies. In our study the vibrating mesh nebulizer outperformed 2 jet nebulizers in each position tested, and the ultrasonic nebulizer either at the ventilator or at the humidifier.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, reviewers found that 25 papers were potentially eligible. Reasons for subsequent exclusion were studies on children >5 years old (n = 12) [11][12][13][14][15][16][26][27][28][29][30][31] ; studies on nonacute patients (n = 4) [32][33][34][35] ; and studies on hospitalized patients (n = 3). [36][37][38] Finally, 6 articles were selected for inclusion in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Lugo et al used a working neonatal ventilated lung model to show that MDIs with spacers provided more efficient delivery of albuterol than jet nebulizers [96]. Fok et al demonstrated a similar trend in vivo wherein an MDI was equally as effective as an ultrasonic nebulizer, and more effective than a jet nebulizer, at delivering salbutamol to the lower respiratory tract of ventilated preterm neonates [97]. Therefore, it is important to consider the method of aerosol generation when employing the intrapulmonary route for delivery to neonates.…”
Section: Intrapulmonarymentioning
confidence: 91%